2017
DOI: 10.3390/rs9080800
|View full text |Cite
|
Sign up to set email alerts
|

How Do Aerosol Properties Affect the Temporal Variation of MODIS AOD Bias in Eastern China?

Abstract: Abstract:The rapid changes of aerosol sources in eastern China during recent decades could bring considerable uncertainties for satellite retrieval algorithms that assume little spatiotemporal variation in aerosol single scattering properties (such as single scattering albedo (SSA) and the size distribution for fine-mode and coarse mode aerosols) in East Asia. Here, using ground-based observations in six AERONET sites, we characterize typical aerosol optical properties (including their spatiotemporal variation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
26
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 34 publications
(33 reference statements)
5
26
0
Order By: Relevance
“…By contrast, the DB10K retrievals are easily underestimated in spring and summer, and overestimated in autumn and winter. Similar seasonal variations of the Aqua-MODIS C6 DT and DB AOD retrievals were analyzed in Eastern China by [32]. Besides, as for the DTB10K retrievals, the positive biases do not exhibit obvious seasonal variations, and are smaller than the other MODIS C6 products.…”
Section: Seasonal Variation Of Aod Retrieval Biassupporting
confidence: 64%
See 3 more Smart Citations
“…By contrast, the DB10K retrievals are easily underestimated in spring and summer, and overestimated in autumn and winter. Similar seasonal variations of the Aqua-MODIS C6 DT and DB AOD retrievals were analyzed in Eastern China by [32]. Besides, as for the DTB10K retrievals, the positive biases do not exhibit obvious seasonal variations, and are smaller than the other MODIS C6 products.…”
Section: Seasonal Variation Of Aod Retrieval Biassupporting
confidence: 64%
“…Both algorithms are unsuitable for snow-covered surfaces. The details about the two retrieval algorithms were already reported in previous researches [29][30][31][32]. The MODIS C6 10 km aerosol product also provides a set of DT and DB combined database (DTB).…”
Section: Modis C6 Datamentioning
confidence: 99%
See 2 more Smart Citations
“…There are many studies conducting to evaluate the accuracies of MODIS AOD, and some researches demonstrated that the aerosol retrieval from satellites has large improvements and with high effectiveness (Li et al, ; Zhang et al, ). Meanwhile, other scholars think that there still are many uncertainties in satellite aerosol data sets (Li et al, ; Tao et al, ; Tao et al, ). However, numerous scholars have compared the MODIS AOD products to the observations from Aerosol Robotic NETwork (AERONET) or China Aerosol Robot Sunphotometer Network (Fan et al, ; Hsu et al, ; Sayer et al, ; Sayer et al, ; Tao et al, ; Wang et al, ; Wei et al, ; Xie et al, ; Yan et al, ), and most of their MODIS aerosol retrievals are from DT algorithm or DB algorithm of C5.1 and C6.…”
Section: Introductionmentioning
confidence: 99%